COMMUNITY LEARNING CENTER (PKBM) PROGRAM EVALUATION BASED ON CONTEXT EVALUATION AS A COMMUNITY LEARNING RESOURCE IN AMBON CITY - Lamberthus Lokollo; Jhoni L Siang (EDU SCIENCES JOURNAL, 2022)
The overall goal of the study is to determine and analyze the utility of PKBM deployment as an educational tool in Ambon Municipality. With a focus on the PKBM program as a hub of resources for community learning in the city of Ambon, this study is evaluation research based on the CIPP evaluation paradigm (context, input, process, and product). This method is superior because it allows for a thorough examination of social phenomena by researchers. In an effort to identify research issues, the research technique is utilized as a manual or tool to aid researchers in carrying out the various parts of the research. The findings demonstrated that the people of Ambon City needed PKBM as a hub for community learning resources, particularly in the wake of the city's social unrest. The community's active participation was required to rebuild educational activities by empowering local talent, particularly that of those who drop out of school or are unable to pursue higher education because of adverse economic circumstances. It can be concluded that the context component (context) of the PKBM package C program in Ambon City has a high or good actuality.